The Transformative Role of Technology in Medical Education - Quispe, Justiniano Felix Palomino (2024)
Introduction: medical education has undergone a remarkable transformation driven by technological advances in recent decades. The progressive integration of digital tools and innovative technologies has significantly enriched access to educational resources and improved clinical practice. Objective: this analysis aims to evaluate the impact of various emerging technologies in medical education and their influence on clinical practice, highlighting improvements in skills and diagnostic accuracy, as well as the personalization of learning. Methods: a comprehensive analysis of pilot studies and systematic reviews was conducted that evaluated the impact of various technologies on medical education. Data collected from leading institutions were examined and statistical techniques were used to evaluate the effectiveness of these technological interventions. Results: pilot studies demonstrated significant improvements in surgical skills and diagnostic accuracy of medical students who benefited from virtual reality and clinical simulators. The application of artificial intelligence and machine learning has also improved the interpretation of medical data and early diagnosis of diseases. Conclusions: the continued integration of emerging technologies into medical education shows promising potential to personalize learning and improve patient care. However, challenges such as data security and appropriate training must be addressed to ensure successful implementation and lasting impact on clinical practice and medical education.